Effect of valproic acid and environmental enrichment on behavioral functions in rats - Kus, Krzysztof; Burda, Kinga; Nowakowska, Elzbieta; Czubak, Anna; Metelska, Jana; Łancucki, Michał; Brodowska, Karolina; Nowakowska, Anna (Arzneimittelforschung, 2010)
Deficits of cognitive functions are perceived as an important pathogenic factor of many neurological and psychiatric diseases. Such symptoms can be a result of a disease process or appear due to applied medication. Epilepsy is a disease in which cognitive deficits can occur before first seizures, during seizures and remissions. Valproic acid (VAL, CAS 77372-61-3) is a medicine applied in order to control epileptic seizures and mood stabilizing in bipolar disorders and mania. Its activity is related to the effect on neurotransmission of many systems.The present study was conducted to investigate whether enriched environment (EE) conditions affect learning and memory, and influence the antidepressant effect in rats.VAL improves spatial memory upon repeated administration both in the rats housed in standard conditions (SC) (after 21 days of treatment) and those housed in enriched environment (as early as after 14 days of treatment). VAL has an antidepressant effect on the forced swimming test both in the rats housed in standard conditions and those housed in EE. In rats housed in EE, the antidepressant effect occurred much earlier (as early as after 7 days of VAL administration). It is worth noting that VAL has a low profile of adverse effects (Activity Meter, chimney test). The correlations observed may be translated into clinical effects, leading to new, more effective VAL therapies in depression or memory disorders in patients with underlying epilepsy.
Keywords: Antiepileptic drugs; CAS 77372-61-3; Enriched environment; Spatial memory; Valproic acid, antidepressant effect